Improving the stability and transdermal permeability of phycocyanin loaded cubosomes - Zhu, Chune; Duan, Wenjuan; Jing, Hui; Long, Jieyu; Huang, Ying; Huang, Di; Wu, Chuanbin (Frontiers in Nanotechnology, 2024)
Instability and low transdermal permeability of protein antioxidants are major obstacles to resist oxidative stress in transdermal drug delivery system. To overcome these shortcomings, cubosomes were developed as an advanced transdermal delivery system to improve stability and transdermal absorption of the model antioxidant phycocyanin in this study. Glyceryl monooleate and poloxamer 407 (P407) were used to prepare cubosomes as carrier matrix and stabilizer, respectively. Phycocyanin loaded cubosomes (PC-cubosomes) were prepared by the emulsification and homogenization method. A 33 full factorial design was used to optimize the cubosome formulations. The final optimal PC-cubosomes possessed an average particle size of 183.2 ± 0.5 nm and a negative surface charge as well as achieved a high encapsulation efficiency of 87.2% ± 2.7%. PC-cubosomes appeared as nano-sized and well-shaped spheres with highly ordered cubical structures. The residual amount of phycocyanin in PC-cubosomes was 3-fold higher than that in the free drug solution after 10 days ultraviolet radiation exposure. In vitro release kinetics of phycocyanin from PC-cubosomes fitted to the Higuchi kinetic model, indicating that phycocyanin released from cubosomes mainly attributed to drug diffusion and dissolution. PC-cubosomes also exhibited higher permeability (39.79 μg⋅cm−2⋅hour−1) across the rat skin than phycocyanin solution (16.33 μg⋅cm−2⋅hour−1). Furthermore, PC-cubosomes were easily taken up by keratinocytes, thereby achieving a prolonged anti-oxidative stress effect. These results therefore suggested that cubosomes could be a promising transdermal delivery system to improve the stability and transdermal permeability of phycocyanin.